In Vitro Potential of the Acetone Leaf Extract and Fractions of Psychotria capensis (Eckl.) Vatke (Rubiaceae) to Combat Co-Infection of Tuberculosis and Helminthiasis - Aro, Abimbola O.; Famuyide, Ibukun M.; Oyagbemi, Ademola A.; Kabongo-Kayoka, Prudence N.; McGaw, Lyndy J. (Frontiers in Pharmacology, 2022)
Co-infection with tuberculosis (TB) and helminths (worms) is an emerging global public health concern with both affecting about one-third of the global population. Worms and Mycobacterium tuberculosis concurrence is an issue of particular significance especially in Africa, coupled with multi-drug resistance and drug-related toxicity complicating their control. Chronic infection with helminths can result in impaired immune responses to TB as well as enhancing failure to TB therapy and BCG vaccination. Antimycobacterial and anthelmintic activities of theacetone extract and fractions of Psychotria capensis were evaluated, as well as their in vitro safety. Nitric oxide inhibitory and immunomodulatory effect of the fractions and crude extract of P. capensis were assessed. Antimycobacterial activity of the extract and fractions were tested against four non-tuberculous mycobacteria (M. smegmatis, M. fortuitum, M. aurum, M. bovis BCG) and pathogenic M. tuberculosis H37Rv while the Egg Hatch Assay (EHA) was used for the anthelmintic test on eggs of Haemonchus contortus. Cytotoxicity was determined against Vero kidney cells while in vitro immune modulation via cytokine production was determined on activated macrophages. The minimum inhibitory concentration (MIC) values of the Psychotria capensis acetone extract and fractions ranged from 39 to 1 250 µg/mL with the crude extract and hexane fraction having the best MIC values (both 39 µg/mL). In the EHA, the inhibitory concentration (IC50) ranged from 160 to 630 µg/mL with the hexane fraction having the best activity. The hexane and chloroform fractions were relatively non-toxic with LC50 values of 290 and 248 µg/mL respectively, while the acetone crude extract (64 µg/mL) and n-butanol fraction (71 µg/mL) were moderately toxic. The SI values (LC50/MIC) ranged from 0.1 to 7.4 with the hexane fraction having the highest value against M. smegmatis (7.4). The hexane fraction had the best dual anthelmintic and antimycobacterial activity and was the least cytotoxic. Pro-inflammatory cytokines such as IL-12p70 were upregulated while IL-10 expression was inhibited by the extracts. Finding alternative or complementary approaches to dealing with TB infections by, amongst other things, reducing the incidence of helminth infestations may lessen the burden of TB, contributing to slowing the spread of multi-drug resistance.